KONSEP PENDIDIKAN ISLAM DAN PENDEKATAN PSIKOLOGI DALAM MENANGKAL PAHAM RADIKALISME - Faqihatin Faqihatin; Maslakhatul Ainiyah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
In modern era, Islamic religious learning with the concept of instant learning with incomplete understanding has the potential for critical and radical attitudes. And in a fundamental understanding, things like this trigger the notion of radicalism which can damage the meaning of religion. This is because they have not fully implemented religious teachings and the true meaning of religion has been passed down to humans. In the process of learning Islamic religious education, where students have time to study independently more freely than in the past, today they can access learning resources, learning media both text, audio, video and other forms so that the need for intensity of learning contemporary Islamic religion and psychological approach to them in order to suppress radicalism in their ideas and behavior.